EFEK HALO DAN KEPUTUSAN AUDIT: STUDI EKSPERIMENTAL PENGUJIAN BENTUK DAN CARA PENYAJIAN INFORMASI - Octavian, Nico; Utami, Intiyas (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2016)
AbstractAuditors have limited cognitive in managing information. The form of information presented visually and non-visually can trigger halo effect. This study aims to investigate the accuracy of an audit judgment when the information is served visually and non-visually and the information presentation affects halo effect. This experimental design 2 x 2 between subjects in which 64-bachelor degree students of Accounting Department that assigned as an internal auditor. The result shows that the group who gets the treatment of information presentation in visual forms and order of information positive-negative triggers the positive halo effect and impact to an audit judgment with low accuracy.Keywords: Halo Effect, Information Presentation, Audit Judgement